The Topology of Nation-State: Borders, Territoriality, Sovereignty and War - Bülent ŞENER (Gazi Akademik Bakış)
Borders have been embraced as a clear and unquestionable fact from the perspective of nation-states, which are the fundamental components of the modern international system that emerged with the Peace of Westphalia (1648). From the state’s perspective, borders shaped based on territoriality along with the advent of the modern state are among the leading causes of war in international relations as areas of uncertainty, risk, and opportunity. When the states make their shared goals and problems in different periods be somehow linked to territoriality and/or borders, these problems make the states more prone to war. The findings from empirical research on this issue prove that particularly territorial contiguity (borders) is an essential factor at every stage of the use of force between states. One of the aims of this study is to reveal the relation between the concepts of “border” and “territoriality” with the modern state phenomenon. The second aim of the study is to shed light on the relationship between wars between states and the phenomena of “border” and “territoriality”. For these purposes, first of all, in this study, addressing the phenomenon of territoriality and border in international politics from a historical and sociological perspective, this study examines the emergence of the phenomenon of the nation-state in the international system and the importance and relationship of the concept of “sovereignty,” “territoriality,” and “border” in the determination of the internal and external topology of the state; and accordingly, the relationality between the phenomena of territoriality and borders will be analyzed as the leading cause of inter-state wars.